Collagen dressing versus silver sulfadiazine dressings in partial thickness burns-prospective study - Mathew, Sunil; Shariff, Nawaz; P. N., Sreeramulu; ., Krishnaprasad (International Surgery Journal, 2021)
Background: Occurrence, pathophysiology and management of burns is complex. It is a painful condition and topical management of burns is a challenging task. An ideal topical dressing which allows faster healing with reduction of pain, prevent infection, leads to a good scar formation and which is cost effective is required. Thus, there is a need to study the effectiveness of collagen dressing in comparison with conventional silver sulphadiazine dressing (SSD) in terms of pain score, healing time and cost efficiency. Methods: This prospective randomized comparative study includes patients with partial thickness burns, <40% BSA and not older than 48 hours, admitted to department of surgery of RL Jalappa hospital and research centre Tamaka Kolar during the period December 2019 to March 2020. 34 patients were studied, these patients were randomized into collagen dressing or silver sulphadiazine dressing group of 17 each. Results: The 34 patients admitted with partial thickness burns, <40% BSA were divided into two equal and comparable groups. Patients subjected to collagen dressings were classified under group I and those who underwent 1% silver sulphadiazine dressings were classified as group II. Conclusions: The collagen dressing is more cost effective than SSD. SSD has disadvantage of the large number of dressings prolonged hospital stay, amount pain, loss of time and labour of the patient and the accompanying person which make collagen dressing more cost effective as it is most of the time a single dressing.